Study of breakthrough seizures in newborns with hypoxic-ischemic encephalopathy after stopping anticonvulsant therapy - Malwade, Sudhir; Nayak, Manas; Chalipat, Shiji; Agarkhedkar, Sharad (Indian Journal of Child Health, 2020)
Background: Neonatal seizure is a distinct clinical response to neurological dysfunction. Hypoxic-ischemic encephalopathy (HIE) is a leading cause of neonatal seizures. Neonates with seizures are at risk of neurodevelopmental impairment, cognitive, behavioral disorders, epilepsy in later part of life, and even death during the neonatal period of life. Objective: The objective of the study was to study the occurrence of breakthrough seizures in a newborn with HIE after stopping anticonvulsant therapy. Materials and Methods: The study was a prospective cross-sectional study done in a Level III NICU of a tertiary hospital in Western India. A total of 35 full-term newborns with evidence of perinatal hypoxia with HIE II, III as per Sarnat and Sarnat staging and magnetic resonance imaging were enrolled. Patients with seizures were treated with intravenous phenobarbitone (PB). Patients were observed for breakthrough seizures after discontinuation of PB and were followed up at high-risk outpatient department until 6 months of age. Results: A total of 31 (88.6%) cases of 35 did not manifest breakthrough seizures. There were four (11.4%) cases which manifested breakthrough seizure after stopping anticonvulsant therapy and three had HIE III (p=0.044). Maternal anemia was observed to have a statistically significant association with breakthrough seizures (p<0.0001). There were nine cases with an abnormal neurological examination, three manifested breakthrough seizures, and there was no statistical correlation between neurological examination and occurrence of clinical and breakthrough seizures (p=0.0165). Conclusion: After initial seizure control by anticonvulsant therapy, breakthrough seizures are not increased after withholding the maintenance therapy.